Description of immature stages and adult diagnosis of Stilobezzia coquilletti Kieffer 1917 (Diptera: Ceratopogonidae) - Ronderos, María Marcela; Cazorla, Carla G.; Spinelli, Gustavo Ricardo; Carrasco, Daiane Silveira (Zootaxa, 2008)
The pupa and larva of Stilobezzia (Stilobezzia) coquilletti Kieffer are described, and a diagnosis of the adult is given. All described stages were photomicrographed and illustrated by using phase-contrast microscope, plus Scanning Electron Microscope in the case of the larva. Immature stages were collected in a shallow stream of sandy bottom nearby Manaus, Brazil. The pupa is compared with S. (S.) fiebrigi Kieffer, and the larva with S. (S.) antennalis Coquillett. Copyright © 2008 Magnolia Press.
Keywords: Ceratopogonidae; Diptera; Hexapoda; Stilobezzia Antennalis; Stilobezzia Coquilletti